Pengaruh Persepsi Kemudahan, Persepsi Manfaat Dan Kepercayaan Terhadap Keputusan Penggunaan Uang Elektronik Dengan Sikap Sebagai Variabel Intervening Pada Pengguna Dana Di Universitas Esa Unggul - Rismalia, Rismalia; Sugiyanto, Sugiyanto (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
The main purpose of this study was to determine the perception of convenience, perceived benefits and trust in the decision to use Dana at Esa Unggul University with attitude as an intervention variable. The sampling technique used in this research is purposive sampling with non-probability sampling method. The number of respondents taken as many as 160 respondents with the criteria of superior one student, transactions using Dana at least 2 times within a period of 6 months to 1 year and the application is the owner registered in the Dana application. The analytical method used is path analysis which includes validity, reliability, t-test and coefficient of determination (R²) using the SPSS program. The results showed that perceived convenience, perceived usefulness and trust in the decision to use Dana at Esa Unggul University, perceived convenience, benefits and perceived trust influenced the attitudes of Fund users at Esa Unggul University, and attitude had no effect as an intervention variable between perceived convenience variables, perceived benefits and trust in the decision to use Dana at Esa Unggul University.